European post-consumer steel scrap in 2050: A review of estimates and modeling assumptions - Frank Pothen; Carolin Hundt (Ernst-Abbe-Hochschule Jena, Fachbereich Betriebswirtschaft, 2024)
This paper studies the availability of post-consumer steel scrap in Europe until 2050. We introduce the indicator potentially available domestic post-consumer scrap (PADPS) which measures the amount of (steel) scrap from obsolete products available for recycling, prior to trade in scrap. We analyze material flow studies from the academic literature and international organizations to quantify this indicator. The studies suggest a rising trend of post-consumer scrap amounts until a saturation level when the expected yearly steel product obsolescence of the system stabilizes. Between 2010 and 2050, PADPS is expected to rise annually by approximately 1.6% per year. We identify in-use steel stocks, recycling rates, and product lifetimes as the three commonly gauged factors determining PADPS. While recycling rates and product lifetimes range comparatively close in the studies, the estimation of in-use stocks displays much greater variation and introduces an element of uncertainty in estimating the post-consumer scrap amounts that can be expected in the coming decades. – – Dieser Artikel untersucht die Verfügbarkeit von Stahlschrott in Europa bis zum Jahr 2050. Dazu wird der Indikator PADPS (potentially available domestic post-consumer scrap, potenziell verfügbare inländische Altschrottmenge) eingeführt. Dieser gibt den Anfall von Stahlschrott nach Beendigung des Produktlebenszyklus aber vor internationalem Handel mit Schrotten an. Zu diesem Zweck werden Materialflussanalysen aus Wissenschaft und Industrie analysiert. Die Studien deuten auf einen Trend wachsender Altschrottmengen hin, der sich erst beim Erreichen eines Sättigungslevels auf einem gleichbleibenden Niveau jährlich anfallender Schrottmengen stabilisiert. Zwischen 2010 und 2050 wird ein Anstieg von PADPS von ungefähr 1,6% pro Jahr erwartet. In der Ökonomie befindliche Stahlmengen (Steel Stocks), Recyclingraten und Produktlebenszeiten kristallisieren sich als die Faktoren heraus, die bei der Schätzung von PADPS in Studien am häufigsten bestimmt werden. Recyclingraten und Produktlebenszeiten weisen in den Studien vergleichbare Werte auf. Die Abschätzung der Steel Stocks ist mit größeren Schwankungen behaftet und trägt zu größeren Unsicherheiten bei der Modellierung zukünftig verfügbarer Schrottmengen bei.
urn:nbn:de:gbv:27-dbt-20240319-123427-003
Keywords: 330; Steel scrap; steel recycling; post-consumer scrap; steel stocks; Europe; 2050; literature review; Stahlschrott; Stahlrecycling; Altschrott; Steel Stocks; Europa; 2050; systematische Literaturanalyse